2022
DOI: 10.3389/fimmu.2022.940228
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei X11 Ameliorates Hyperuricemia and Modulates Gut Microbiota in Mice

Abstract: Hyperuricemia (HUA) is the presence of excessive uric acid (UA) in blood, which leads to an increased risk of chronic kidney disease and gout. Probiotics have the potential effect of alleviating HUA. The purpose of this study was to screen probiotics with UA-lowering activity and explore the underlying mechanism. The UA-lowering activity of 20 lactic acid bacteria strains was investigated in vitro, and the effect of candidate probiotics on UA metabolism was evaluated using the HUA Balb/c mouse model. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
(69 reference statements)
2
19
0
Order By: Relevance
“…When rats were treated with L. brevis PDD-5, serum levels of UA, CREA, and BUN were significantly reduced and XOD levels were effectively inhibited. When treated with L. brevis PDD-5, serum levels of UA, CREA, and BUN were significantly reduced and XOD levels were effectively inhibited in rats, which is consistent with the findings of Cao et al [33] . The levels of inosine and guanosine in the intestinal contents after the removal of the organisms were statistically significant in the high-dose group, which was consistent with the results of serum uric acid levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When rats were treated with L. brevis PDD-5, serum levels of UA, CREA, and BUN were significantly reduced and XOD levels were effectively inhibited. When treated with L. brevis PDD-5, serum levels of UA, CREA, and BUN were significantly reduced and XOD levels were effectively inhibited in rats, which is consistent with the findings of Cao et al [33] . The levels of inosine and guanosine in the intestinal contents after the removal of the organisms were statistically significant in the high-dose group, which was consistent with the results of serum uric acid levels.…”
Section: Discussionsupporting
confidence: 91%
“…Wu et al [40] found that Limosilactobacillus fermentum JL-3 inhibited UA-induced changes in the intestinal flora and reduced the ratio of Firmicutes to Bacteroidetes (Firm/Bac ratio) and decreased UA levels. Cao et al [33] found that Lactobacillus paracasei X11 restored intestinal flora α-diversity and reduced hyperuricemia. Some studies have reported a direct correlation between the expression of inflammatory factors and changes in the intestinal flora [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Tissue was harvested immediately after mice had been sacrificed. According to a method stated previously, 17 liver tissue and kidney tissue were cut into dimensions of 0.8 × 0.8 cm. The ileum was cut into dimensions of 1 × 1 cm.…”
Section: Methodsmentioning
confidence: 99%
“…16 However, these clinical therapies have limitations. For example: dietary restriction leads to nutritional imbalance; 17 addition of UOX produces H 2 O 2 and causes bone damage; 18 use of ALLO causes kidney stones. 14,19 Hence, it is necessary to seek new strategies for the treatment of HUA.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the results of previous studies, the relative abundance of Firmicutes was observed to decrease and the relative abundance of Bacteroidetes increased in HUA mice [ 49 ]. The elevated Bacteroidetes / Firmicutes ratio is a feature of microbiota disruption induced by hyperuricemia, and the anti-hyperuricemia probiotics Lactobacillus plantarum Q7 and X11 reduce the Bacteroidetes / Firmicutes ratio and modulate the intestinal flora structure in HUA mice [ 64 , 65 ]. A similar change was observed in this study, whereby MOS supplementation reversed the Bacteroidetes / Firmicutes ratio.…”
Section: Discussionmentioning
confidence: 99%